Factors affecting on females’ employment in the urban informal sector in Colombo district, Sri Lanka. - Perera, E. L. Sunethra J.; Manel, Kanthi (My University, 2017)
The study of labour force participation in the informal sector is very useful for implementing and formulating employment opportunities and human resource development policy programs. Contribution of informal sector employment in nonagricultural sector to the labour force of Colombo district is approximately 44 percent in 2013. One important characteristic of the informal sector is that it has become a major employer of the female labour force in non- agricultural sector in urban population in Colombo district. In this view present study was carried out to explore the socio-economic and demographic factors affecting the employment status of women in informal sector economic activities of the urban settlement communities in Colombo district. The primary data was gathered from a cross sectional sample survey in selected urban areas in the Colombo Municipal Council area and the data was collected from 222 females which were selected based on random manner. To achieve the objectives, both descriptive and logistic regression methods were applied for the data analysis. The results show that low level education is one of the important factors affecting women’s employ with the self-employments. The qualitative findings also discovered that most women of the urban communities have faced environmental factors and poverty, lack of awareness and encouragement to the education and other skills, lack of resources and facilities to start an own business. These findings suggest that efforts to address the problem of women’s access to the self- employment or formal sector occupation in urban labour market.
Keywords: Labour force, socio-economic, self-employments, informal sector, formal sector